Siplizumab Induces NK Cell Fratricide Through Antibody-Dependent Cell-Mediated Cytotoxicity - Binder, Christian; Sellberg, Felix; Cvetkovski, Filip; Berg, Stefan; Berglund, Erik; Berglund, David (Frontiers in Immunology, 2021)
The glycoprotein CD2 is expressed on T and NK cells and contributes to cell-cell conjugation, agonistic signaling and actin cytoskeleton rearrangement. CD2 has previously been shown to have an important function in natural NK cell cytotoxicity but to be expendable in antibody-mediated cytotoxicity. Siplizumab is a monoclonal anti-CD2 IgG1 antibody that is currently undergoing clinical trials in the field of transplantation. This study investigated the effect of CD2 binding and Fc γ receptor binding by siplizumab (Fc-active) and Fc-silent anti-CD2 monoclonal antibodies in allogeneic mixed lymphocyte reaction and autologous lymphocyte culture. Further, induction of NK cell fratricide and inhibition of natural cytotoxicity as well as antibody-dependent cytotoxicity by these agents were assessed. Blockade of CD2 via monoclonal antibodies in the absence of Fc γ receptor binding inhibited NK cell activation in allogeneic mixed lymphocyte reaction. In contrast, siplizumab increased NK cell activation in both mixed lymphocyte reaction and autologous lymphocyte culture due to FcγRIIIA binding. However, experiments using purified NK cells did not show an inhibitory effect of CD2 blockade on natural cytotoxicity or antibody-dependent cytotoxicity. Lastly, it was shown that siplizumab induces NK cell fratricide. Concluding, siplizumab is a promising biopharmaceutical drug candidate for depletion of T and NK cells with minimal off-target effects.